Integrating 3Rs approaches in WHO guidelines for the batch release testing of biologicals: Responses from a survey of vaccines and biological therapeutics manufacturers. (February 2023) - Lilley, Elliot; Coppens, Emmanuelle; Das, Pradip; Galaway, Francis; Isbrucker, Richard; Sheridan, Sarah; Stickings, Paul; Holmes, Anthony
Abstract: The UK National Centre for the Replacement, Refinement, and Reduction of Animals in Research (NC3Rs) has been tasked by the World Health Organization (WHO) to review the extent to which animal-based testing methods are described in their manuals, guidelines and recommendations for vaccines and biotherapeutics. The aim is to identify and recommend where updates to these documents can lead to an increased and more harmonised adoption of 3Rs principles (i.e. Replacement, Reduction and Refinement of animal tests) in the quality control and batch release testing requirements for vaccines and biotherapeutics. Developing recommendations that are widely applicable by both the manufacturers and national regulatory authorities for vaccines and biologicals globally requires a detailed understanding of how different organisations view the opportunities and barriers to better integration of the 3Rs. To facilitate this, we developed and distributed a survey aimed at vaccine and biotherapeutics manufacturers in July 2021. In this paper, we present the key findings from this survey and how these will help inform the recommendations for wider integration of 3Rs approaches by WHO in their guidance documents applicable to the quality control and batch testing of vaccines and biotherapeutics.